2005
DOI: 10.1111/j.1572-0241.2005.30511.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Fecal Incontinence in a Large Community Study of Older Individuals

Abstract: These cross-sectional analyses offer promising evidence that this common condition is correlated with the presence of certain conditions (e.g., stroke and diabetes) and use of certain psychoactive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
5
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 26 publications
8
68
5
3
Order By: Relevance
“…While studies (14,15) of the relationship between AI and diabetes have had conflicting results, we found that AI was associated with having diabetes among obese women only, whereas the relationship between AI and diabetes in women who were not obese was not statistically significant.…”
Section: Prevalence Of Pfds Among Women With Diabetescontrasting
confidence: 88%
See 1 more Smart Citation
“…While studies (14,15) of the relationship between AI and diabetes have had conflicting results, we found that AI was associated with having diabetes among obese women only, whereas the relationship between AI and diabetes in women who were not obese was not statistically significant.…”
Section: Prevalence Of Pfds Among Women With Diabetescontrasting
confidence: 88%
“…It has been suggested that the most likely reason for the increase in risk is microvascular compromise, leading to damage to the urethral sphincter mechanism and bladder sensitivity, and that stricter glycemic control may reduce the risk or severity of urinary incontinence (13). Studies (14,15) of the relationship between anal incontinence and diabetes have had conflicting results.…”
mentioning
confidence: 99%
“…Not surprisingly, stroke survivors perceived their general health to be poorer than the non-stroke population, and a larger proportion also reported having difficulties with daily activities (Table 1). 8 In the overall population major fecal incontinence (soiling of underwear or more on a monthly basis) was reported in 1.5% (n=580). Stroke survivors reported a significantly higher prevalence of any fecal incontinence than the non-stroke population, 7.4% compared with 2.9% (see Table 1).…”
Section: Comparison Between the Stroke And Non-stroke Populationmentioning
confidence: 98%
“…Medical conditions such as diabetes, diarrhea, obesity, neurologic diseases, and urinary incontinence may result in or contribute to the symptoms of fecal incontinence. 1,2,6 In some patients, the etiology of fecal incontinence can be multifactorial. It is critical to establish the cause of incontinence because it is an important determinant of the treatment approach.…”
Section: Current Management Of Fecal Incontinencementioning
confidence: 99%
“…A prevalence up to 12% has been previously reported. 1,2 Men and women of all ages can be affected by fecal incontinence, although studies suggest it is more prevalent with increasing age. 3 In a large community-based study, the prevalence of fecal incontinence was 0.9% in adults between the ages of 40 and 64 years and 2.3% in adults older than 65 years.…”
Section: Introductionmentioning
confidence: 99%